Transformasi Digital Sekolah melalui Implementasi Smart School: Studi pada SMP Negeri 3 Makassar - Ahmad Restani (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
Digital transformation in education encourages schools to adopt the Smart School concept as a strategy to improve the quality of technology-based educational services. This study aims to analyze the implementation of the Smart School concept in supporting educational management effectiveness and improving learning quality in schools. The research employed a qualitative approach using descriptive study methods through observation, interviews, and documentation of information technology utilization in school management and learning processes. The findings indicate that Smart School implementation is supported by the integration of digital technology into school administration systems, digital-based learning platforms, strengthening teachers’ digital literacy competencies, and integrated educational data management. Technology utilization enhances academic service efficiency, management transparency, and flexible student-centered learning practices. However, several challenges remain, including limited technological infrastructure, disparities in teachers’ digital competencies, and organizational readiness to adapt to technology-driven changes. The study concludes that Smart School represents a strategic innovation for developing adaptive education in the digital era; however, its success requires policy support, human resource capacity development, and sustainable digital ecosystem strengthening within schools.